A possible source for Dante’s landscape of the Violenti contro Dio - Modesto, Diana (Spunti e Ricerche, 2016)
Cantos XIV-XVII of Inferno deal with those who have sinned by "malizia con forza" against God. According to traditional criticism these are blasphemers in Canto XIV, sodomites in Cantos XV and XVI and usurers in Canto XVII. The landscape in which these various sinners are punished is generally considered to have been derived from the punishment visited upon the cities of Sodom and Gomorrah as recounted in Genesis XIX. This source for the imagery of these four cantos has been almost universally accepted. This leaves unexplained why the punishment of the sodomites should be shared equally by the blasphemers and the usurers. It is argued that the landscape specifically recalls the heretical theory of the eternity of the world.